Síntese e caracterização de monômeros azo-carbonatos para a preparação de poli(azo-carbonato)s e poli)azo-uretana)s - Capitão, Rebeca Monique [UNESP] (2015)
Aromatic azo-compounds have a wide range of applications, such as textile, pharmaceutical, cosmetics, food, technology (as lasers, liquid crystal displays and electro-optical devices) and advanced organic synthesis. The first part of this work describes the synthesis of azo-dialcohol compounds in good yields. These compounds were chareacterized by NMR, IR and UV-VIS spectroscopy and by mass spectrometry with electrospray ionization (ESI-MS). Moreover, theoretical calculation were performed to determine the influence of the psubstituent group at the wavelength of maximum absorption of the spectra of UV-vis. Following, we discuss the preparation of azo-carbonates monomers by two synthetic routes. One way by direct reaction of the diol and DMC and another by coupling of aryldiazonium salts with bis-carbonate. Finally, we tested the reactivity of azo-carbonate monomers in the polycondensation reaction with a diol or a diamine using TBD as a catalyst for the formation of poly(azo-carbonate) or poly(azo-urethane), respectively. The TBD catalyst was efficient for the reaction of polycondensation and the structures of the copolymers were confirmed by FT-IR, NMR and MALDI-TOF, allowing determinate the different end-groups of the polymer chains formed